2021
DOI: 10.1007/s10965-021-02863-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc isophthalate on the crystallization and crystal transformation behavior of polybutene alloy

Abstract: The slow crystallization rate and crystal transformation restrict the application of PB-A (PB blended with 2-3wt% polypropylene). This paper investigated the effects of zinc isophthalate (ZnIA) on the crystallization and crystal transformation behavior of PB-A by means of DSC, POM, XRD and Flash DSC. The results showed that addition of ZnIA raised the crystallization peak temperature from 71.1 ℃ to 82.8 ℃ and decreased the half crystallization time from 818 s to 160 s at the content of 0.2wt%. It also reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…22,28,29 Fantinel 50 found that nano-montmorillonite not only acted as a nucleating agent by increasing the melt crystallization temperature of form II, but also accelerated the subsequent II–I transition at room temperature. Similar experimental observations have been reported after addition of ZnIA, 51 MWCNT, 52 or β-NA. 53 Kaszonyiova 29,54 further extended their work on processes of melt-II, III–I and III–II transitions of iPB-1.…”
Section: Introductionsupporting
confidence: 89%
“…22,28,29 Fantinel 50 found that nano-montmorillonite not only acted as a nucleating agent by increasing the melt crystallization temperature of form II, but also accelerated the subsequent II–I transition at room temperature. Similar experimental observations have been reported after addition of ZnIA, 51 MWCNT, 52 or β-NA. 53 Kaszonyiova 29,54 further extended their work on processes of melt-II, III–I and III–II transitions of iPB-1.…”
Section: Introductionsupporting
confidence: 89%